2015
DOI: 10.1080/10926771.2015.1002654
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Child and Adult Sexual and Physical Trauma among Deaf Adults

Abstract: The purpose of this study was to evaluate the consequences of sexual and physical trauma among a sample of deaf adults. Thirty-two men and 45 women completed the Life Event Checklist (LEC), the Clinician Administered PTSD Scale (CAPS), the Trauma Symptom Inventory (TSI), the Somatoform Dissociation and a sociodemographic questionnaire. In this sample, 40.6% of the male participants and 53.3% of the female participants had experienced some type of sexual trauma during their lifetimes. Physical trauma was repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…First, some studies provided accessible measures according to the type of disability. For example, studies conducted among deaf people included questionnaires translated into sign language (Kvam, 2004; Schild & Dalenberg, 2015) and video recordings, including instructions provided in sign language (Kvam, 2004). Moreover, different strategies were used in studies among people with intellectual or developmental disabilities to enhance their understanding of the questionnaires.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, some studies provided accessible measures according to the type of disability. For example, studies conducted among deaf people included questionnaires translated into sign language (Kvam, 2004; Schild & Dalenberg, 2015) and video recordings, including instructions provided in sign language (Kvam, 2004). Moreover, different strategies were used in studies among people with intellectual or developmental disabilities to enhance their understanding of the questionnaires.…”
Section: Resultsmentioning
confidence: 99%
“…In the first, Schenkel et al (2014) found that child maltreatment (including sexual abuse) was a significant predictor of re-abuse, an effect that was much stronger among deaf and hard of hearing children. In the second study, Schild and Dalenberg (2015) found an association between a history of CSA in deaf children and sexual as well as physical trauma in adulthood. In addition, one study associated the sexual abuse of children with intellectual disabilities with the experience of intimate partner violence as adults (Catani & Sossalla, 2015).…”
Section: Implications Of Csa Among Cwdsmentioning
confidence: 89%
See 1 more Smart Citation
“…Often the ability to reach health-care is restricted due to the difficulty of communication, which sometimes increases the risk of these persons to get the wrong diagnosis or being maltreated. In one of the first large-scale trauma studies with the Deaf community, the California Deaf Trauma Study [41][42][43] discuss the result of hearing loss as having psychosocial consequences and suggest that the term information deprivation trauma (IDT) to describe this. IDT is a concept that requires a negative emotional response that is characterized by "(a) A lack of understanding of the extent, magnitude, consequences, and probability of a current or impending meaningful event; and (b) An inability to access information about this event that would reasonably allow a person to prepare, appropriately respond, or self-protect" [43].…”
Section: Traumatization In Deaf and Hard Of Hearing Individualsmentioning
confidence: 99%
“…During one of the first large-scale trauma studies with the Deaf community, the California Deaf Trauma Study (Schild, 2007;Schild & Dalenberg, 2012a, 2012b, 2015, a common theme emerged that has not yet been adequately addressed in the trauma literature: information deprivation trauma (IDT). The purpose of this article is to expand on our brief introduction of IDT (see Schild & Dalenberg, 2012b) and to provide a more in-depth analysis of the concept, explore various examples in both hearing and deaf samples, and discuss assessment issues.…”
mentioning
confidence: 99%